2004
DOI: 10.1159/000078319
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological and Microbiological Study of Brucellosis in Kuwait

Abstract: Objective: The primary objective of the study was to determine the prevalence of brucellosis and the antimicrobial susceptibility pattern of local Brucellae isolates in the Infectious Diseases Hospital, Kuwait. Subjects and Methods: A single serum sample was collected from each of 1,836 patients of different nationalities from January 2000 to December 2001. Any patient with a provisional diagnosis of fever or brucellosis had a standard tube agglutination (STA) test for the quantitation of Brucella antibodies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
4
16
1
Order By: Relevance
“…The 32%of positive blood cultures found in this study are within the 15–90% range reported in previous studies [1,14]. Differences in isolation rates between centers may be due to delay in diagnosis and previous antibiotic usage of the patients before admission to clinics.…”
Section: Discussionsupporting
confidence: 73%
“…The 32%of positive blood cultures found in this study are within the 15–90% range reported in previous studies [1,14]. Differences in isolation rates between centers may be due to delay in diagnosis and previous antibiotic usage of the patients before admission to clinics.…”
Section: Discussionsupporting
confidence: 73%
“…The agent PD 131628 was the only quinolone for which no crossresistance of a ciprofloxacin-resistant strain was found in another study by Qadri et al (50), although an increased MIC for the drug was noted against this strain. On the other hand, in two recent studies, one from Turkey (13) and one from Kuwait (21), all isolates were susceptible to ciprofloxacin, whereas 9.6% and 8% of the isolates were resistant to rifampin in vitro, respectively.…”
Section: Laboratory Studiesmentioning
confidence: 82%
“…Thus, it will not be surprising if resistance of Brucella melitensis to quinolones will increase as well in the future. It should also be noted that resistance of Brucella to rifampin may represent an issue for consideration, judging by the results of some recent in vitro studies (13,21). As Baykam et al have also commented (13), this fact may be linked to the increased use of rifampin in some areas due to the reemergence of tuberculosis.…”
Section: Critical Evaluation Of the Available Evidencementioning
confidence: 99%
“…Intermediate rifampin susceptibility elsewhere in Turkey has been described previously (1). Limited in vitro susceptibility to rifampin and trimethoprim-sulfamethoxazole in Kuwait (5) and Mexico (9) has similarly been reported.…”
mentioning
confidence: 94%